Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Berpikir Kreatif Siswa Di Kelas IV SDN 122332 Pematang Siantar - Lenny Marlina Malau; Asister Fernando Siagian; Radode Kristianto Simarmata (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Discovery Learning is an innovation in learning because students' creative thinking abilities are truly optimized through a systematic group work or film process, so that students can empower, hone, test and develop their thinking abilities on an ongoing basis. The purpose of this research is to determine the effect of the Discovery Learning model on the creative thinking abilities of Class IV students at SDN 122332 Pematang Siantar. The analysis shows that in general the educational learning model can influence student learning outcomes in class IV at UPTD SDN 122332 Pematang Siantar. With a sample size of 23 students, it can be seen that the percentage of pretest results was 17% and the percentage of posttest results was 65%. From the percentage results, it can be seen that student learning outcomes after being given treatment using the Discovery Learning model are classified as increasing.